Effectiveness of Group Guidance Services Using Self-Management Techniques to Prevent Addiction to Online Game Use (In SMA Negeri 2 Sungai Limau) - Succy Primayuni; Neviyarni Neviyarni (Universitas Negeri Padang, 2020)
This research is motivated by the phenomenon that students spend 5-6 hours playing online games, do not eat on time, and do not care about the social environment because playing online games is more interesting according to them. Students also often play games in class if the teacher is boring, students often want to go home quickly to be able to play games in thearnet, in a day students are able to play games 2-3 hours, and during school holidays students play online games for up to 4 hours more a day. This study aims to: (1) Describe students' online game addictions before being given group guidance services, management, and (4) Describe the differences in online game addiction of students in groups that are given group guidance services and groups that are provided with group guidance services using self-management techniques. . The subjects of this study were students of class X SMA Negeri 2 Sungai Limau, registered in 2019/2020, amounting to 30 people. The research instrument used was an online game addiction questionnaire. Data were analyzed using descriptive statistical techniques and the Test Difference technique with the help of the SPSS For Windows 20.0 program. The results of the study revealed that (1) the results of the analysis of the pretest data obtained information that the addiction of the online game of SMA Negeri 2 Sungai Limau students was in the High category (2) the results of the posttest data analysis in the experimental group provided group guidance services using self management techniques obtained information that addicted to the online game of Sungai Limau High School 2 students in the Low category, (3) The results of the posttest data in the control group provided group guidance services without using self management techniques obtained information that the addiction of online games of Sungai Limau High School 2 students was in the Medium category, (4) the results of hypothesis testing using SPSS 20.0 obtained information that there is a significant difference between the experimental group and the control group. This means that the hypothesis proposed in the study is accepted where group guidance services using effective self management techniques to prevent addiction to playing online games.